The patio as a place. Legacy and the contemporaneous in the Casa Huarte - Olalquiaga Bescós, Pablo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
José Antonio Corrales and Ramón Vázquez Molezún designed in 1966 a house for the family of Jesús Huarte, one of the most important businessmen and art collectors in Spain. The project for the Casa Huarte was born of the place where it was inserted through a non-conventional method: it developed from the negation of its physical context. It is a defensive project, fortified against the street, hostile and noisy, and opens up to interior courtyards, creating an idyllic interior world, isolated visually and acoustically from the street. Its development questioned the Modern Movement’s approach toward compact courtyard-houses, whose paradigm were Mies’ projects for courtyard-houses and their built prototype: the Sert House in Cambridge while at the same time feeding on a classical legacy. Corrales and Molezún adapted certain traditional interventions in landscape to modernity through the use of courtyards, from the sequence of heterogeneous courtyards of Pompeian and ottoman architecture to the relationship between internal and immediate external space in traditional Japanese architecture. The result was a novel courtyard-house, decidedly modern, that reflected a new concept of intervention in landscape.
Keywords: Patrio; Corrales and Molezún; House of the Faunus; Sinan; Katsura; Modern Movement